Panel autoregressive distributed lag (ARDL) approach for investigating the tourism driven growth in South Asia - Sankaran, A. (South Asian Journal of Socio-Political Studies)
Tourism is a modern industry, which promotes socio-economic development in many ways. The positive and significant role played by the tourism industry in different corners of the economy & society was well documented in the literature. To examine the causal relationship between tourism and economic development in the South Asian region is a value addition to the existing body of knowledge. Against this empirical issue, the present study attempts to estimate the functional relationship between tourism and economic development and also the role of tourism in employment generation. To pursue this research, secondary data on the total number of tourist arrivals, the total amount of revenue earned from tourism, total employment have been collected from various sources such as World Development Indicators, World Travel and Tourism Council, World Tourism Organization, the Statistics and Facts of Global Travel and Tourism Industry and OECD for the period from 2000 to 2020 for South Asian countries. The collected data have been processed using PMG method in the umbrella of Panel ARDL approach of cointegration followed by causality to capture the multi-dimensional causal relationship among the variables. In general, the result gives evidence for the existence of the tourism-led growth hypothesis enhancing economic progress in South Asia. The result of the exercise revealed some interesting insights for policymaking. As tourism activities like tourist arrival and tourism expenditure positively influence GDP, the policymakers should focus on these activities to tape the potential of tourism. Thereby we can employ unemployed youth, thus enhancing growth.- Reproduced
Keywords: Tourism-led growth hypothesis, South Asian region, panel cointegration